Pemberdayaan Kelompok Wanita Tani “Barokah” melalui Inovasi Pembuatan Produk Olahan Nanas di Desa Semen Kec. Gandusari Blitar - Sungkawati, Endang; Yuniwati, Eny Dyah; Hernanik, Nova Dwi (Universitas Tribhuwana Tunggadewi Malang, 2024)
Pineapple is a leading commodity in Semen Village, Gandusari District, and Blitar Regency. One of its varieties, Banasari Pineapple, is known to have yellow flesh and high water content. Currently, processed pineapple products from Blitar are still limited and lack variety. The problem is that the fresh and abundant pineapple from the harvest in Semen Village has not been widely processed; it is only sold fresh, and pineapple juice is produced by KWT